Chapter António Correia: o homem e seu legado literário - Bruxo, Jorge (Studi di Traduzione Letteraria Lusofona, 2023)
The personal memory of Lurdes Escaleira and Jorge Bruxo deals with the relationship among them, Correia and Ernesto Matos and focuses on a first portrait of António Correia and his literary